The Effect of Verbal Working Memory Intervention on the Reading Performance of Students with Specific Learning Disabilities - Mehmet Okur; Veysel Aksoy (Behavioral Sciences)
The purpose of this study is to investigate the effects of verbal working memory (VWM) interventions on reading speed, accuracy, and comprehension in elementary school students diagnosed with specific learning disabilities (SLD). Given the limited research on the role of VWM in reading performance, this study fills a critical gap in the literature. A pre-test and post-test design was employed, with an experimental group (n = 14) receiving VWM interventions over 4 weeks, while the control group (n = 12) received no intervention. The intervention focused on enhancing VWM and verbal short-term memory (V-STM) through structured cognitive tasks, including rehearsal techniques and phonological loop strengthening activities, delivered over 24 sessions. Results showed that although VWM interventions significantly enhanced VWM capacity (t(24) = 3.39, p < 0.05, d = 1.48), they did not lead to significant improvements in reading speed or accuracy. However, a statistically significant improvement in reading comprehension was observed (p = 0.04, d = 0.92). These findings suggest that while enhancing VWM may not directly improve reading fluency, it can positively affect comprehension. The study highlights the importance of considering VWM in educational interventions targeting reading comprehension and recommends further research into other cognitive and linguistic factors influencing reading speed and accuracy. Additionally, future studies should explore the long-term effects of diverse intervention strategies on reading outcomes.